APPLICATION OF MULTI-DEGREE-OF-FREEDOM SYSTEM IN VIBRATION ISOLATION DESIGN OF OPTOELECTRONIC POD - WANG PengPeng; JIA HongGuang; XUE ZhiPeng; LI Ming; GUAN YongLiang (Jixie qiangdu)
To reduce the airborne vibration influence of airborne optoelectronic pod on quality,a small optical pod antivibration isolation system was designed according to multi-degree-of-freedom system vibration theory,vibration isolation theory and current vibration environment. This vibration isolation system can configure optical pod isolation system natural frequency effectively. The natural frequency of the isolation system was determined through multi-degree-of-freedom system vibration theory,instruct the design of spatial layout and relative positions,damping values and stiffness of isolators,and support structure. The simulation analysis of optical pod isolation system was conducted by using ADAMS/Vibration code module,the optical pod isolation system was tested on a vibration table,the experiment results of natural frequency were consistent with theoretical and simulation results,the error is less than 10%,and the isolation system has good vibration isolation performance near 92 Hz. The field test image effects also prove the damping effectiveness of small optical pod anti-vibration isolation system.